Особливості сезонного розвитку та поліваріантність структури річних квітконосних пагонів Pulsatilla patens (L.) Mill. і P. Pratensis (L.) Mill. в умовах київського мегаполісу - Scherbakova, O.F.; Novosad, K.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of studying of changes of the structure annual flowering shoots of Pulsatilla patens (L.) Mill. and P. pratensis (L.) Mill. during vegetation period are represented. Their structural, rhythmological, morphometric (dimensional) multivariate are established.